The barefoot road - Dingle, Brian Clinton (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2015)
My novella is set in South Africa in a post-apocalyptic world. The drone technology theorised for the near future is widespread and scattered survivors live under the constant threat of drone strikes. The protagonist tries to negotiate these dangers and the looming threat of a slave empire to reconnect with his friends and family. He encounters bizarre hallucinations and flashbacks as a result of exposure to an unidentified gas.
Keywords: South African fiction (English) -- 21st century; Creative writing (Higher education); South African fiction (English) -- Study and teaching (Higher)